Power Characteristics Analysis of Maximum Power Point Tracking (MPPT) and Pulse Width Modulation (PWM) - Ilham Ramadhana Chofananda; Jamaaluddin Jamaaluddin; Arief Wisaksono; Izza Anshory (Procedia of Engineering and Life Science, 2021)
Solar energy is a source of energy and has advantages compared to fossil energy. Indeed, further research and development of this type of solar power is needed, including at the University of Muhammadiyah Sidoarjo. The use of solar energy is carried out by installing photovoltaic (PV) cells with a photovoltaic output control system that uses MPPT (Maximum Power Point Tracking) and PWM (Pulse Width Modulation) to regulate the load used and charge the battery. The two PV control methods have different characteristics. These differences will be analyzed based on the characteristics of the load and sunlight contained in the electrical engineering laboratory of the Muhammadiyah University of Sidoarjo. It can be seen from the results of the analysis that at power above 200 W, MPPT has a better voltage stability than PWM.